The Legacy of the “Cyprus Codex” (MS. Torino J.II.9): Creating New Technologies and Compositions through a Collaborative Process - Sammoutis, Evis; Sheppard Skaerved, Peter; Hsu, Timothy (Circuit, 2018)
MS. J.II.9 (also known as the “Cyprus Codex”) is an anonymous Codex composed in the court of Nicosia in the first part of the 15th century during Cyprus’s Frankish period and the Lusignan Dynasty. It is the only known Codex of Western music in the region and one of the few exclusively French codices known from that time. Its style lies in the threshold between Ars Nova and Ars Subtilior with unique features. Composer Evis Sammoutis, violinist Peter Sheppard Skaerved and Music technology professor Timothy Hsu have built a collaboration inspired by the legacy of MS. J.II.9. This resulted in the creation of new bows and techniques of performing the violin and the creation of new compositions based both on the material from MS. J.II.9 and technological advancements.